2017
DOI: 10.1111/ejh.12920
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of homologous recombination DNA repair genes in the early and advanced stages of myelodysplastic syndrome

Abstract: Our study demonstrates that the expression of DNA repair factors, primarily RAD51 and XRCC2, is deregulated in patients with MDS and presents a specific pattern with respect to prognostic categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The XRCC2 gene expression level in this patient was significantly decreased by more than 4-fold and was comparable to other patients with monosomy 7 or complex karyotype. As described in our previous study, the XRCC2 gene showed significantly lower levels of expression in the group of MDS patients with chromosome 7 abnormalities than in the rest of the MDS patients [21]. Decreased expression levels were also present for all genes functionally connected with mutated XRCC2 : ATM , BRCA1 , BRCA2 , MRE11A , RAD51 , RAD51B , RAD51C , RAD51D , and RAD52 .…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The XRCC2 gene expression level in this patient was significantly decreased by more than 4-fold and was comparable to other patients with monosomy 7 or complex karyotype. As described in our previous study, the XRCC2 gene showed significantly lower levels of expression in the group of MDS patients with chromosome 7 abnormalities than in the rest of the MDS patients [21]. Decreased expression levels were also present for all genes functionally connected with mutated XRCC2 : ATM , BRCA1 , BRCA2 , MRE11A , RAD51 , RAD51B , RAD51C , RAD51D , and RAD52 .…”
Section: Discussionsupporting
confidence: 57%
“…The number of various genetic and cytogenetic alterations described in the last few years [5-7, 9] and our recent results showing deregulated DNA repair gene expression in MDS cases [21] support the theory that MDS is a disease of genomic instability [10]. Though mutations in the TP53 gene and their relationship with MDS are already known, no mutations in genes directly involved in DNA repair have been described.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Aberrations in DNA damage response/repair genes other than TP53 and some genes involved in DNA damage checkpoints are rare. Differential expression of homologous recombination DNA repair-associated genes during MDS progression was detected and could be confirmed as new biomarkers related to pathogenesis and poor prognosis in MDS [17,18].…”
Section: Advances In Our Knowledge Of Cytogenetic Abnormalities and Gmentioning
confidence: 79%